2010
DOI: 10.1021/cg100560s
|View full text |Cite
|
Sign up to set email alerts
|

Facile Chemical Synthesis of Nanocrystalline Thermoelectric Alloys Based on Bi−Sb−Te−Se

Abstract: High yield syntheses of size-confined Bi2Te3 and Sb2Te3 nanocrystals and nanoflakes, and their alloys, were carried out by a facile glycol-mediated solvothermal process. Phase purity and good crystalline quality were achieved for all alloy compositions by this synthesis process. The isotropically and anisotropically shaped nanocrystals were obtained without using any capping molecule, template, or ligand. Plausible growth mechanisms have been proposed. Densification via spark plasma sintering allowed for dense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 44 publications
0
35
1
Order By: Relevance
“…However, these results represent a potential approach towards reducing κ L signifi-cantly at low temperatures. If we note that doping of TE materials can readily be accomplished by chemical synthetic approaches, [17,18] and the fact that SPS densification can provide dense polycrystalline TE materials with nanoscale grains or inclusions, [14][15][16][17][18] this work represents a new direction towards enhanced TE properties of FeSb 2 . Further study into doping of the FeSb 2 nanocrystals before densification is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…However, these results represent a potential approach towards reducing κ L signifi-cantly at low temperatures. If we note that doping of TE materials can readily be accomplished by chemical synthetic approaches, [17,18] and the fact that SPS densification can provide dense polycrystalline TE materials with nanoscale grains or inclusions, [14][15][16][17][18] this work represents a new direction towards enhanced TE properties of FeSb 2 . Further study into doping of the FeSb 2 nanocrystals before densification is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…In this process, we solely rely on hydrazine monohydrate for reduction, rather than both glycol and hydrazine, as has been done earlier [4,18]. The powders extracted after room temperature reactions were analyzed by XRD and found that both Bi 0.5 Sb 1.5 Te 3 and Bi 2 Te 2.7 Se 0.3 powders are purely amorphous and do not show any diffraction peak.…”
Section: Resultsmentioning
confidence: 99%
“…Bi 0.5 Sb 1.5 Te 3 and Bi 2 Te 2.7 Se 0.3 have been synthesized by modifying and extending the ethylene glycol mediated solvo-thermal process [18]. For synthesis of both these nanomaterials, bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O), antimony chloride (SbCl 3 ), selenium oxide (SeO 2 ) and sodium tellurite (NaTeO 3 ) have been used as Bi, Sb, Se and Te sources respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The p-type semiconductor, bismuth antimony telluride (Bi x Sb 2−x Te 3 ), has a high ˛2 , resulting in an excellent ZT value (normally about 1.0 at 50-150 • C) [14,[31][32][33]. In addition, some research groups have endeavored to fabricate nanobulk Bi 0.5 Sb 1.5 Te 3 to reduce Ä [34][35][36][37][38]. Thus, the highest ZT value, 1.4 at 100 • C has been achieved with this material [24].…”
Section: Introductionmentioning
confidence: 99%